Komunitas Virtual Menjadi Komunitas Sosial - Suryo Nugroho, Hanif; Afifi, Subhan; Rochayanti, Christina (Paradigma: Jurnal Masalah Sosial, Politik, dan Kebijakan, 2019)
Social community is one of the social groups that grow in society. The Community of Info Cegatan Jogja (ICJ) has applied a long process for the formation of a virtual community. Starting from social media Facebook, ICJ community evolved into a virtual community and more active in doing activity after a meeting between the member. This purpose of this study is to find out how the process of formation of virtual communities into social communities within the Community of Info Cegatan Jogja (ICJ). is to explain the concept of virtual reality in the virtual community phenomenon. While the framework used in this study is Computer Mediated Communication and Virtual Reality Community so that can explain how the process of communication in detail about the formation of virtual reality in the virtual community until computer-mediated communication can form a community in real. The type of this research use a qualitative research in order to obtain a conclusion. The researcher chose the Ethnography method that will be implemented in both virtual and real space. The results of this study indicate that in a process the formation of social communities into virtual communities through several phases including: community meetings, Pseudo community, conflict, emptiness, the formation of virtual communities. In addition, it can be concluded that the definition of community continues to be redefined along with the development of communication and information technology. The key to understanding the community as a social community is when each member has a desire to achieve a common goal. It is also commonly found in the ICJ community, either when they are only engaged in virtual / online or after doing meeting in real life